(untitled) (Community Based Medical Journal, 2018)
Anemia is a global public health problem affecting 305 million school children (SC) worldwide. It has deleterious effects in SC, including lower school achievement due to impaired cognitive development and physical growth, fatigue and poor attention span, and increased morbidity because of reduced resistance to infection. The school age is a dynamic period of growth and development. During this period physical, mental, social development of child takes place. The purpose of the study is to observe the anemia among the school aged children and to compare the urban and rural children as well as to see the correlation between malnutrition and anemia. A school-based cross sectional study was conducted on a total of 600 School Children from 10 school, aged from 6-10 years old children of Mymensingh district. Study was conducted for a period of one year from October 2009 to September 2010. Two staged stratified random sampling method were employed to select study participants. Data on socio-demographic and socio-economic characteristics, and dietary status of children were collected using pre-tested structured questionnaire through face-to-face interview of children’s caregivers. Anthropometric measurements were taken. Hemoglobin (Hb) concentration was determined by using cyanmethaemoglobin method. Datawas analyzed by computer programmed SPSS version 14.0. P-value < 0.05 was considered as statistically significant. Among the primary school children in Seventy one percent of our primary school children were anemic. Rural children were more sufferers in anemia. CBMJ 2018 January: Vol. 07 No. 01 P: 24-29